If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -48 = 5x + -3 Reorder the terms: -48 + 14x = 5x + -3 Reorder the terms: -48 + 14x = -3 + 5x Solving -48 + 14x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -48 + 14x + -5x = -3 + 5x + -5x Combine like terms: 14x + -5x = 9x -48 + 9x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 -48 + 9x = -3 + 0 -48 + 9x = -3 Add '48' to each side of the equation. -48 + 48 + 9x = -3 + 48 Combine like terms: -48 + 48 = 0 0 + 9x = -3 + 48 9x = -3 + 48 Combine like terms: -3 + 48 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| 18-4x=7x-7 | | 2y-80=y+9 | | 2y-80=y+90 | | 10x-24=8x+12 | | X+30=2x | | 4[2x-5(x-3)]=6 | | 10-4x=6-2x | | 36+340=2 | | 7x(2)+x-8=0 | | 9x(x-2)=9x^2+40 | | 6w-14w=-72 | | -7(x+4)-11=16+8 | | 3(2x-5)+9=12 | | 20n=m | | m=20n | | 2x-2y+z=7 | | x-4-13x-2+36=0 | | x^2-16x-29=0 | | (11b-8)-5(2b+4)=-6 | | 9m=7 | | 8x+6x+3+9=9x+5+4x | | 2y^2+2y+2=14 | | x^2+5x-6=2x+4 | | 15x+15y=8xy | | -9(v+4)+3v+5=5v+12 | | 7p+8=16+6p | | S(t)=-16t^2+64t+80 | | C(x)=5x^2-30x+81 | | 18w-(16w)= | | 8(4x+4)-4-6= | | 3x^2+-29x+40=0 | | m(p+2)=n |